Bimetallic nano alloy architecture on a special polymer: Ni or Cu merged with Pd for the promotion of the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling - Patil, Vijay P.; Kashid, Abhijit A.; Solanki, Bhanupratap S.; Kharul, Ulhas K.; Iyer, Suresh (Journal of Chemical Sciences, 2021)
Novel Ni-Pd and Cu-Pd bimetallic nano alloys was designed and heterogenized on the highly robust ABPBI [poly(2,5-benzimidazole)] polymer in high yields using NaBH4 as reducing agent. These were versatile ligand free catalysts for the Mizoroki-Heck reaction and Suzuki-Miyaura coupling. The bimetallic Ni-Pd-ABPBI catalyst for the Mizoroki-Heck reaction of 4-iodo anisole could be recycled 5 times with high yields. Aryl bromides could also be activated for the Mizoroki-Heck reaction using Cu-Pd-ABPBI NP catalysts, with moderate yields. Graphic abstractSynopsis Novel bimetallic Ni-Pd and Cu-Pd nano alloys, heterogenized on the robust ABPBI [poly(2,5-benzimidazole)] polymer using NaBH4 as reducing agent, is described. These were versatile ligand free, noble metal conservative catalysts, for the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling. Aryl bromides were activated for the Mizoroki-Heck reaction using the Cu-Pd-ABPBI catalyst.
Keywords: Bimetallic nano alloys; Cu-Pd-ABPBI; Mizoroki-Heck reaction; Ni-Pd-ABPBI; Suzuki coupling

Highly efficient chemoselective hydrogenation of 5-HMF to BHMF over reusable bimetallic Pd-Ir/C catalyst - Ratrey, Geetanjali; Solanki, Bhanupratap S.; Kamble, Sanjay P.; Rode, V. Chandrashekhar (ChemistrySelect, 2022)
Catalytic synergism was observed for a bimetallic Pd-Ir catalyst supported on activated carbon for chemoselective hydrogenation of 5-hydroxymetahyl furfural (5-HMF) to 2, 5-(bishydroxymethyl) furan (BHMF) with complete conversion and 97 % selectivity under very mild reaction conditions. The structural characterization like XRD, N-2 sorption, FE-SEM and TEM suggested formation of fine nanoparticles (1.95-3.08 nm) having very higher surface area, uniform distribution and mesoporous nature of the material. XPS spectra and Pyridine-IR spectroscopy revealed formation of Pd-PdO and Ir/IrO2/IrO3 interface on the catalytic surface along with strong Bronsted acidic sites which were responsible for high efficiency of catalyst at 80 degrees C, 100 psig H-2 pressure at 5-HMF/Catalyst=20 and within 2.5 h of reaction time. A plausible reaction mechanism is also elucidated based on structure activity correlation.
Keywords: 5-HMF; Carbon; Catalytic synergism; Selective hydrogenation; Valorization

Bimetallic quantum dots (Cu-Pd, Ni-Pd) catalyzed reaction of bromo arenes with alkenes and aryl boronic acids - Raut, Pallavi K.; Meroliya, Heena K.; Dumbre, Swapnil R.; Patil, Vaishali N.; Solanki, Bhanupratap S.; Waghmode, Shobha A.; Iyer, Suresh (Indian Journal of Chemistry, 2023)
Bimetallic quantum dots (Cu-Pd and Ni-Pd) are active ligand-free catalysts for the alkenylation and arylation of aryl bromides. The catalysts are easy to synthesize by benign green protocols and characterized by various techniques. The bimetallic QD catalysts synthesized thus are superior to Pd(OAc)2 or other Pd NP catalysis of alkenylation reactions of aryl bromides with similar E-selectivity. The reaction of aryl bromide with aryl boronic acid is facile with high yields.
Keywords: Aryl bromides; Bimetallic QDs catalysis; Cu-Pd; Mizoroki-Heck; Ni-Pd; Suzuki coupling